WEBVTT
00:00:00.600 --> 00:00:15.600
Find the equation of a sphere that passes through the points π΄ nine, zero, zero; π΅ three, 13, five; and πΆ 11, zero, 10, given that its center lies on the π¦π§-plane.
00:00:16.800 --> 00:00:22.160
One of the most natural ways to express the equation of a sphere is in the so-called standard form.
00:00:22.760 --> 00:00:35.760
In general, we write the standard form of the equation of a sphere as π₯ minus π₯ naught squared plus π¦ minus π¦ naught squared plus π§ minus π§ naught squared equals π squared.
00:00:36.320 --> 00:00:42.400
π₯ naught, π¦ naught, and π§ naught are the coordinates of the center of the sphere and π is its radius.
00:00:42.760 --> 00:00:50.640
The sphere itself is then the collection of all the points with coordinates π₯, π¦, and π§ that satisfy this equation.
00:00:51.280 --> 00:01:00.720
What makes this form so natural and useful is that specifying the center of a sphere and its radius is enough to completely determine the entire sphere.
00:01:01.440 --> 00:01:10.520
And given the equation of a sphere in standard form, we merely need to look at the equation to determine the coordinates of the center of the sphere and its radius.
00:01:11.040 --> 00:01:18.760
In our case, though, we donβt know the radius of the sphere and all we know about the center is that it lies on the π¦π§-plane.
00:01:19.520 --> 00:01:22.560
We are, however, given three points that lie on the sphere.
00:01:23.160 --> 00:01:44.040
So to find the equation of the sphere, weβll take the coordinates of each of these points, plug them into our standard form for the equation of a sphere, and use this to arrive at a system of equations that we can then solve to determine the center of the sphere and its radius, which will then give us the general equation of the sphere.
00:01:44.560 --> 00:01:47.160
We actually already know one of the coordinates of the center of the sphere.
00:01:47.560 --> 00:01:52.880
Because the center of the sphere lies in the π¦π§-plane, the π₯-coordinate is zero.
00:01:53.560 --> 00:01:58.880
Letβs now plug the points π΄, π΅, and πΆ into our standard form equation.
00:01:59.360 --> 00:02:05.160
For π΄, π₯ is nine, π¦ is zero, and π§ is also zero.
00:02:05.880 --> 00:02:16.720
So we have nine minus zero squared because π₯ naught is zero plus zero minus π¦ naught squared plus zero minus π§ naught squared equals π squared.
00:02:17.160 --> 00:02:25.960
Nine minus zero is just nine, zero minus π¦ naught is negative π¦ naught, and zero minus π§ naught is negative π§ naught.
00:02:26.560 --> 00:02:28.560
Nine squared is 81.
00:02:28.960 --> 00:02:35.400
Negative π¦ naught squared is negative π¦ naught times negative π¦ naught, which is positive π¦ naught squared.
00:02:35.760 --> 00:02:39.920
And likewise, negative π§ naught squared is positive π§ naught squared.
00:02:40.360 --> 00:02:46.360
So 81 plus π¦ naught squared plus π§ naught squared equals π squared.
00:02:46.880 --> 00:02:49.920
Now weβll do the same calculation for point π΅.
00:02:50.400 --> 00:02:54.840
We have π₯ is three, π¦ is 13, and π§ is five.
00:02:55.560 --> 00:03:00.960
The only easy simplification we can make is that three minus zero squared is nine.
00:03:01.480 --> 00:03:07.960
For now, weβll leave 13 minus π¦ naught squared and five minus π§ naught squared as they are.
00:03:08.640 --> 00:03:17.120
So our second equation is nine plus 13 minus π¦ naught squared plus five minus π§ naught squared equals π squared.
00:03:17.480 --> 00:03:26.080
Our last equation will come from point πΆ which has π₯ equals 11, π¦ equals zero, and π§ equals 10.
00:03:26.440 --> 00:03:43.160
Now we have 11 minus zero squared, which is 11 squared or 121; zero minus π¦ naught squared, which we know is just π¦ naught squared; and 10 minus π§ naught squared, which we wonβt expand for the time being.
00:03:43.800 --> 00:03:52.880
So our third equation is 121 plus π¦ naught squared plus 10 minus π§ naught squared equals π squared.
00:03:53.400 --> 00:04:00.760
Now we have a system of three equations in three variables: π¦ naught, π§ naught, and π.
00:04:01.480 --> 00:04:05.680
To solve this system, weβll work one variable at a time.
00:04:06.080 --> 00:04:12.760
Note that all three expressions on the left-hand side are equal to the same expression on the right-hand side, namely, π squared.
00:04:13.320 --> 00:04:20.840
So we can create an equation without π in it by equating any two expressions from the left-hand side of these equations.
00:04:21.520 --> 00:04:29.360
Also note that in the first and third equations, the only appearance of π¦ naught is in the single term π¦ naught squared.
00:04:29.920 --> 00:04:44.920
So by equating the left-hand sides of the first and third equations, we should be able to eliminate not only π, but also π¦ naught, which will leave us with a single equation in the single unknown π§ naught.
00:04:45.520 --> 00:04:57.240
So we have 81 plus π¦ naught squared plus π§ naught squared equals 121 plus π¦ naught squared plus 10 minus π§ naught squared.
00:04:57.720 --> 00:05:04.680
And we know this equality holds because both expressions are equal to the same thing, π squared.
00:05:05.200 --> 00:05:06.760
Now we need to simplify.
00:05:07.320 --> 00:05:11.360
Weβll start by subtracting 81 and π¦ naught squared from both sides.
00:05:11.960 --> 00:05:19.600
81 minus 81 is zero, as is π¦ naught squared minus π¦ naught squared.
00:05:20.200 --> 00:05:24.120
So on the left-hand side, weβre just left with π§ naught squared.
00:05:24.720 --> 00:05:35.000
On the right-hand side, 121 minus 81 is 40 and π¦ naught squared minus π¦ naught squared is again zero.
00:05:35.800 --> 00:05:41.560
So this leaves us with π§ naught squared equals 40 plus 10 minus π§ naught squared.
00:05:42.080 --> 00:05:49.120
Now look what we have: exactly what we wanted, a single equation with the single unknown π§ naught.
00:05:49.520 --> 00:05:55.400
To solve for π§ naught, we need to expand 10 minus π§ naught squared on the right-hand side.
00:05:55.880 --> 00:06:03.240
This gives us π§ naught squared equals 40 plus 100 minus 20π§ naught plus π§ naught squared.
00:06:03.680 --> 00:06:07.720
This has actually worked out more nicely than we mayβve originally thought.
00:06:08.160 --> 00:06:14.160
The fact that we have a π§ naught squared on one side suggests that we have a quadratic equation.
00:06:14.560 --> 00:06:19.840
But we have the same π§ naught squared on the other side of the equation.
00:06:20.400 --> 00:06:23.440
So, in fact, this equation is linear and easy to solve.
00:06:24.080 --> 00:06:30.640
To solve this equation, weβll subtract π§ naught squared from both sides and add 20π§ naught to both sides.
00:06:31.240 --> 00:06:35.880
On both sides of the equation, π§ naught squared minus π§ naught squared is zero.
00:06:36.400 --> 00:06:40.240
This leaves us with 20π§ naught on the left-hand side.
00:06:40.880 --> 00:06:49.280
And on the right-hand side, 40 plus 100 is 140 and negative 20π§ naught plus 20π§ naught is zero.
00:06:49.800 --> 00:06:57.160
So 20π§ naught equals 140 and dividing both sides by 20, π§ naught equals seven.
00:06:57.680 --> 00:07:06.760
Now that we have a value for π§ naught, the only two variables left are π and π¦ naught.
00:07:07.320 --> 00:07:21.240
To find π¦ naught, weβll equate the expression on the left-hand side of the first and second equation because we know that equating the first and third equation eliminates π¦ naught from the calculation.
00:07:21.600 --> 00:07:25.680
But we need π¦ naught in the calculation to find its value.
00:07:26.240 --> 00:07:46.600
So we have 81 plus π¦ naught squared plus π§ naught squared equals nine plus 13 minus π¦ naught squared plus five minus π§ naught squared, where again we know this equality holds because both sides are equal to π squared.
00:07:47.120 --> 00:07:55.000
To turn this equation into a single equation with a single variable, all we need to do is plug in π§ naught equals seven.
00:07:55.680 --> 00:08:03.760
Now we have a single equation with a single variable and all thatβs left to do is solve for π¦ naught.
00:08:04.360 --> 00:08:08.400
Letβs start by simplifying and expanding all of the squares that we can.
00:08:08.880 --> 00:08:11.960
For starters, seven squared is 49.
00:08:12.360 --> 00:08:17.480
Five minus seven is negative two and negative two squared is positive four.
00:08:17.880 --> 00:08:28.240
Finally, we expand 13 minus π¦ naught squared to 169 minus 26π¦ naught plus π¦ naught squared.
00:08:28.720 --> 00:08:37.440
Collecting all the numerical terms, on the left-hand side, we have 81 plus 49, which is 130.
00:08:38.160 --> 00:08:42.240
So the left-hand side is 130 plus π¦ naught squared.
00:08:42.760 --> 00:08:50.120
And on the right-hand side, we have nine plus 169 plus four, which is 182.
00:08:50.760 --> 00:08:58.840
So the right-hand side is 182 minus 26π¦ naught plus π¦ naught squared.
00:08:59.320 --> 00:09:09.160
We see again that what originally looked like a quadratic equation is in fact linear because we have the same squared term on both sides.
00:09:09.680 --> 00:09:18.480
Subtracting π¦ naught squared from both sides gives us 130 equals 182 minus 26π¦ naught.
00:09:19.040 --> 00:09:28.800
Now we add 26π¦ naught and subtract 130 from both sides, which gives us 26π¦ naught equals 52.
00:09:29.400 --> 00:09:34.360
It follows then by dividing both sides by 26 that π¦ naught is two.
00:09:35.000 --> 00:09:40.520
The last quantity we need to determine is π or, more precisely, π squared.
00:09:41.000 --> 00:09:47.240
To find this, weβll simply substitute seven for π§ naught and two for π¦ naught in our first equation.
00:09:47.720 --> 00:09:53.280
So 81 plus two squared plus seven squared is π squared.
00:09:53.640 --> 00:10:03.480
That is, 81 plus four plus 49 is π squared and π squared is 134.
00:10:04.280 --> 00:10:10.440
We now have all four quantities that we need to express the equation of our sphere in standard form.
00:10:10.960 --> 00:10:22.440
The equation of our sphere in standard form is π₯ minus zero squared plus π¦ minus two squared plus π§ minus seven squared equals 134.
00:10:23.280 --> 00:10:30.960
Letβs express this equation in another form where we will expand out all the squares and have the right-hand side of the equation equals zero.
00:10:31.680 --> 00:10:33.960
π₯ minus zero squared is π₯ squared.
00:10:34.280 --> 00:10:39.440
π¦ minus two squared is π¦ squared minus four π¦ plus four.
00:10:39.880 --> 00:10:45.680
π§ minus seven squared is π§ squared minus 14π§ plus 49.
00:10:46.520 --> 00:10:51.720
And weβve set the right-hand side equal to zero by subtracting 134 from both sides.
00:10:52.400 --> 00:10:58.680
Just to tidy up this expression a little bit, weβll collect the three quadratic terms together, then the two linear terms.
00:10:59.120 --> 00:11:10.440
And finally, collecting the constant terms, four plus 49 minus 134 is negative 81, and this whole expression equals zero.
00:11:11.200 --> 00:11:22.600
π₯ squared plus π¦ squared plus π§ squared minus four π¦ minus 14π§ minus 81 equals zero is the equation of a sphere that weβre looking for.
00:11:23.040 --> 00:11:32.160
And we got this equation from the equation of the sphere in standard form, which we found by solving for the coordinates of the center of the sphere and the square of its radius.